1987
DOI: 10.1128/aac.31.5.698
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind evaluation of ceftazidime dose ranging in hospitalized patients with cystic fibrosis

Abstract: Eighty-five patients with cystic fibrosis who were experiencing an acute infectious exacerbation of their disease were randomized in double-blind fashion to receive either 50 or 75 mg of ceftazidime per kg (body weight) per dose administered intravenously every 8 h for 14 days. Three patients were dropped from the study within 4 days of enrollment for reasons unrelated to drug administration. The total daily dose of ceftazidime administered was restricted by protocol design and was independent of the body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This is similar to the results of a recent study, which found nonmucoid strains to be more resistant than mucoid strains to seven antimicrobial agents. 20 Similar observations have been noted for aminoglycosides and ciprofloxacin. 21,22 In contrast, one study found mucoid isolates to have higher MICs than nonmucoid isolates with ceftazidime, piperacillin, and amikacin.…”
Section: Discussionsupporting
confidence: 71%
“…This is similar to the results of a recent study, which found nonmucoid strains to be more resistant than mucoid strains to seven antimicrobial agents. 20 Similar observations have been noted for aminoglycosides and ciprofloxacin. 21,22 In contrast, one study found mucoid isolates to have higher MICs than nonmucoid isolates with ceftazidime, piperacillin, and amikacin.…”
Section: Discussionsupporting
confidence: 71%
“…Optimal treatment of infections by P. aeruginosa (28) is crucially important, as it is almost impossible to eradicate chronic lung infections by this pathogen in CF patients. Ceftazidime is still the cephalosporin with the best activity against P. aeruginosa (45) and is a valuable treatment option in antipseudomonal therapy in CF patients (6,12,61,69).…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical calculation of the dosing of ceftazidime demonstrates that the previously recommended doses of <200 mg . kg -1 [97] may still be too low for treating CF patients [70] when given intermittently. Meropenem was given at a dose of 40 mg .…”
Section: Intravenous Antipseudomonal Antibiotic Therapy In Cystic Fibmentioning
confidence: 99%
“…The effectiveness of the various penicillins seems to be similar [42]. From the third generation cephalosporins, ceftazidime particularly is effective against P. aeruginosa [85,97]. Similarly, no differences were found in effects on clinical condition, pulmonary function, or P. aeruginosa sputum counts when different aminoglycosides were compared with each other such as tobramycin with gentamicin or with netilmicin [42].…”
Section: Intravenous Antipseudomonal Antibiotic Therapy In Cystic Fibmentioning
confidence: 99%